2015
DOI: 10.1002/jmr.2523
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a thermostable antinociceptive lectin isolated from Andira anthelmia

Abstract: Andira anthelmia (tribe Dalbergieae), a plant from Brazilian Amazon, possesses a seed lectin that was purified by affinity chromatography in sepharose-mannose. This novel Dalbergieae lectin, named AAL, agglutinated rabbit erythrocytes treated with trypsin. The hemagglutinating activity of AAL was maintained after incubation at a wide range of temperature (40 to 70 °C) and pH, was shown to be dependent on divalent cations, and was inhibited by d-mannose and d-sucrose. AAL showed an electrophoretic profile in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…This study demonstrated the modulator effect of the puri ed Andira anthelmia lectin (AAL) on vascular and cellular events of acute in ammation in rats, that was shown to be dependent on the lectin domain. These results corroborate the AAL antinociceptive effect previously in the in ammatory phase of the formalin test [8].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study demonstrated the modulator effect of the puri ed Andira anthelmia lectin (AAL) on vascular and cellular events of acute in ammation in rats, that was shown to be dependent on the lectin domain. These results corroborate the AAL antinociceptive effect previously in the in ammatory phase of the formalin test [8].…”
Section: Discussionsupporting
confidence: 91%
“…Andira anthelmia lectin (AAL) was isolated by sepharose-mannose a nity chromatography, presenting binding a nity for mannose and glucose [8]. Animals received AAL (0.01; 0.1; 1 mg/kg) or 0.9% NaCl (sterile saline) by intravenous (i.v.)…”
Section: Lectin Isolation and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, those possessing binding affinity for N-acetylglucosamine present systemic anti-inflammatory effect, such as the lectins of Lonchocarpus sericeus (Alencar et al 2005, Napimoga et al 2007 and Lonchocarpus araripensis (Pires et al 2016). In addition, Dalbergiae lectins possessing binding affinity for mannose present pro-inflammatory and nociceptive effects, such as the lectins of Centrolobium tomentosum (Almeida et al 2016) and Platypodium elegans (Araripe et al 2017, Cavada et al 2018, except for the lectin of Andira anthelmia, which presents antinociceptive effect (Nascimento et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 One exception is Andira anthelmia lectin since it demonstrated an inhibitory effect on the inflammatory phase of the formalin test. 11 Other Dalbergieae lectins that possess N-acetyl-D-glucosamine affinity present anti-inflamma tory properties, such as those of Lonchocarpus sericeus, 12,13 Lonchocarpus araripensis, 14,15 and Lonchocarpus campestris. 16 The galactosebinding lectins show proinflammatory effects, such as that elicited by Vatairea macrocarpa [17][18][19] and Vatairea guianensis.…”
mentioning
confidence: 99%